Preparation method of conductive machine-made sand and conductive machine-made sand

CN122958088APending Publication Date: 2026-10-23STATE GRID ZHEJIANG ELECTRIC POWER CO LTD JINHUA POWER SUPPLY CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611205348.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]但是,现有导电机制砂在与水泥等材料混合使用时,需要经历搅拌、输送和成型等过程,其导电性能容易发生变化,导致制得的水泥基材料电学响应不够稳定,影响其感知结果的可靠性

Benefits of technology

[0015]可选的,所述第二次微波辐照处理过程中,所述活化机制砂表面的温度为60~100℃。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958088A_ABST
    Figure CN122958088A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of conductive machine-made sand and the conductive machine-made sand, and relates to the field of building materials, and comprises the following steps: first microwave irradiation coupling lye activation treatment is carried out on the machine-made sand to obtain activated machine-made sand; the first microwave irradiation coupling lye activation treatment comprises the following steps: the machine-made sand is placed in an alkaline solution and is subjected to activation treatment under microwave irradiation, and the irradiation treatment time is 1-10 min; a polymer binder, a conductive filler, a dispersing agent and water are mixed to obtain a conductive coating liquid; the activated machine-made sand is mixed with the conductive coating liquid; the activated machine-made sand is subjected to second microwave irradiation treatment, and the treatment time is 10-30 s; the conductive filler is fixed in a bonding phase formed by the polymer binder dried into a film through microwave irradiation to form a composite conductive layer on the surface of the activated machine-made sand, and the conductive machine-made sand is obtained; wherein, at least part of the conductive fillers are overlapped to form a conductive path. The application improves the conductive stability of the prepared conductive machine-made sand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials, specifically to a method for preparing conductive manufactured sand and the conductive manufactured sand itself. Background Technology

[0002] Self-sensing cement-based materials are a class of functional building materials that can reflect stress, deformation, or damage states through changes in their own electrical parameters. They can be used in scenarios such as structural health monitoring, road load sensing, and component damage early warning. To enable cement-based materials to have electrical response capabilities, existing technologies typically introduce conductive fillers into cement, mortar, or concrete to build a conductive network within the material. Conductive manufactured sand is a functional aggregate in which conductive components are introduced onto the surface of sand particles or fine aggregates. It can serve as a carrier for conductive fillers in the preparation of cement-based materials. Compared to directly incorporating conductive fillers into the cement matrix, conductive manufactured sand can form conductive pathways through the spatial distribution of aggregates within the cement-based material, thereby endowing the cement-based material with functions such as resistance response, strain sensing, or damage monitoring.

[0003] Existing conductive manufactured sand typically involves loading conductive components onto the surface of sand grains or fine aggregates, thereby imparting conductivity to the originally high-resistivity aggregates. In this way, the conductive components can distribute throughout the cementitious material along with the aggregates, thus participating in the formation of a conductive network. Compared to directly adding conductive fillers to the cement matrix, this type of conductive manufactured sand solution helps reduce the impact of uneven dispersion of conductive fillers within the cement matrix on the continuity of the conductive network and improves the utilization efficiency of the conductive fillers.

[0004] However, when existing conductive manufactured sand is mixed with materials such as cement, it undergoes processes such as mixing, conveying, and molding, during which its conductivity is prone to change. This results in unstable electrical responses in the produced cement-based materials, affecting the reliability of their sensing results. Therefore, improving the conductivity stability of conductive manufactured sand is a technical problem that needs to be solved in this field. Summary of the Invention

[0005] This invention aims to address, to a certain extent, one of the technical problems in related technologies. To this end, this invention provides a method for preparing conductive manufactured sand and conductive manufactured sand, thereby improving the conductive stability of the prepared conductive manufactured sand.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing conductive manufactured sand includes the following steps: The manufactured sand was subjected to a first microwave irradiation coupled with alkaline solution activation treatment to obtain activated manufactured sand; The first microwave irradiation coupled alkaline solution activation treatment includes: placing the manufactured sand in an alkaline solution and performing activation treatment under microwave irradiation conditions for 1 to 10 minutes; A conductive coating liquid is obtained by mixing a polymer binder, a conductive filler, a dispersant and water, wherein the polymer binder is one or more of polyvinylpyrrolidone, polyvinyl alcohol or polyacrylic acid; The activated manufactured sand is mixed with the conductive coating liquid, so that the conductive coating liquid adheres to the surface of the activated manufactured sand; The activated mechanical sand with the conductive coating liquid attached is subjected to a second microwave irradiation treatment for 10-30 seconds. The conductive filler is fixed in the adhesive phase formed by the polymer adhesive after microwave irradiation and drying to form a composite conductive layer on the surface of the activated mechanical sand, thereby obtaining the conductive mechanical sand. In this embodiment, at least some of the conductive fillers overlap each other to form a conductive path.

[0007] In this application, a composite conductive layer is formed through a series of steps including a first microwave irradiation coupled with alkaline activation treatment of manufactured sand, coating with a conductive coating liquid, and further microwave irradiation treatment. This allows the conductive filler to be stably maintained on the surface of the manufactured sand. The alkaline activation treatment makes the surface of the manufactured sand more suitable for wetting and adhesion of the conductive coating liquid, providing a surface basis for the formation of the composite conductive layer. The conductive coating liquid contains both a polymer binder and conductive filler, allowing the conductive filler to adhere to the activated manufactured sand surface along with the polymer binder. After a second microwave irradiation treatment, the polymer binder forms a bonding phase on the surface of the activated manufactured sand, and the conductive filler is fixed in or on the surface of this bonding phase, thereby forming the composite conductive layer. Because at least some of the conductive filler overlaps to form conductive pathways, the composite conductive layer, while possessing conductivity, can also maintain the spatial position of the conductive filler on the aggregate surface with the help of the bonding phase. Therefore, compared with schemes where the conductive filler relies solely on physical adsorption to adhere to the aggregate surface, this application can reduce the possibility of the conductive filler detaching from the aggregate surface during disturbances such as stirring, transportation, and molding, allowing the conductive pathways to be more stably maintained on the surface of the manufactured sand, thereby improving the conductive stability of the conductive manufactured sand.

[0008] Optionally, the alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution, and the concentration of the sodium hydroxide solution or the potassium hydroxide solution is 0.5-2 mol / L; in the first microwave irradiation coupled alkaline solution activation treatment, the microwave irradiation power is 300-1000 W, and the irradiation treatment time is 2-8 min.

[0009] Optionally, in the second microwave irradiation treatment, the power of the microwave irradiation treatment is 200~800W.

[0010] Optionally, after the first microwave irradiation coupled alkaline solution activation treatment, the manufactured sand is washed with water until neutral and dried to obtain the activated manufactured sand; the manufactured sand is artificial sand obtained by crushing, shaping and screening rocks, with a silica content of 50% to 75% and a particle size of 0.08 to 5 mm.

[0011] Optionally, the conductive filler is one or more of graphene, graphene oxide, carbon nanotubes, and carbon black.

[0012] Optionally, when the conductive filler is graphene, the graphene sheet diameter is 5–15 μm and the thickness is 5–10 nm.

[0013] Optionally, the dispersant is one or more of melamine dispersants, sodium dodecylbenzene sulfonate, or polycarboxylate superplasticizers; the polymer binder, the conductive filler, the dispersant, and water are mixed and then subjected to mechanical stirring and / or ultrasonic dispersion treatment to obtain the conductive coating liquid.

[0014] Optionally, by mass, the manufactured sand is 1000 parts, the conductive filler is 1-5 parts, the polymer binder is 5-15 parts, the dispersant is 0.5-2 parts, and the water is 20-60 parts.

[0015] Optionally, during the second microwave irradiation treatment, the temperature of the activated mechanical sand surface is 60–100°C.

[0016] Furthermore, the present invention also provides conductive manufactured sand, which is obtained by the aforementioned method for preparing conductive manufactured sand. The reasoning process for the beneficial effects of the conductive manufactured sand provided by the present invention and the aforementioned method for preparing conductive manufactured sand is similar, and will not be repeated here.

[0017] These features and advantages of the present invention will be disclosed in detail in the following specific embodiments and accompanying drawings. The preferred embodiments or means of the present invention will be shown in detail in conjunction with the accompanying drawings, but are not intended to limit the technical solutions of the present invention. In addition, each of these features, elements and components appearing in the following text and drawings is a plurality of, and different symbols or numbers are used for convenience of representation, but all represent parts with the same or similar construction or function. Attached Figure Description

[0018] The present invention will be further described below with reference to the accompanying drawings: Figure 1 This is a schematic diagram of the preparation process of conductive manufactured sand in an embodiment of the present invention; Figure 2Macroscopic morphology images of GS conductive manufactured sand prepared in Comparative Example 3, GE conductive manufactured sand prepared in Comparative Example 2, and GP conductive manufactured sand prepared in Example 1. Figure 3 Scanning electron microscope (SEM) images of GS conductive machined sand prepared in Comparative Example 3, GE conductive machined sand prepared in Comparative Example 2, and GP conductive machined sand prepared in Example 1. Figure 4 The graph shows the conductivity test results of GS conductive manufactured sand prepared in Comparative Example 3, GE conductive manufactured sand prepared in Comparative Example 2, and GP conductive manufactured sand prepared in Example 1. Figure 5 The graph shows the stability test results of GS conductive manufactured sand prepared in Comparative Example 3, GE conductive manufactured sand prepared in Comparative Example 2, and GP conductive manufactured sand prepared in Example 1. Figure 6 Raman spectra of graphene (GNP), GP conductive manufactured sand prepared in Example 1, GE conductive manufactured sand prepared in Comparative Example 2, GS conductive manufactured sand prepared in Comparative Example 3, and manufactured sand. Detailed Implementation

[0019] Embodiments of the present invention are described in detail below, examples of which are illustrated in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described are intended to explain the present invention and should not be construed as limiting the invention.

[0020] The terms "an embodiment," "example," or "example" used in this specification refer to a particular feature, structure, or characteristic described in connection with the embodiment itself that may be included in at least one embodiment disclosed in this application. The phrase "in an embodiment" appearing in various places throughout the specification does not necessarily refer to the same embodiment.

[0021] This application provides a method for preparing conductive manufactured sand. For example... Figure 1 As shown, this method uses manufactured sand as the carrier. The surface state of the manufactured sand is improved through a first microwave irradiation coupled with alkaline activation treatment. Then, a conductive coating liquid containing polymer binder, conductive filler, dispersant, and water is applied to the surface of the activated manufactured sand. After a second microwave irradiation treatment, the activated manufactured sand is dried, and a composite conductive layer is formed on its surface, thus obtaining conductive manufactured sand. The resulting conductive manufactured sand is not made conductive by changing the internal composition of the manufactured sand, but rather by constructing a composite conductive layer containing conductive filler on the surface of the manufactured sand, enabling the originally high-resistivity sand particles to acquire surface conductivity.

[0022] The composite conductive layer refers to the layered structure formed on the surface of activated mechanical sand after the conductive coating liquid removes moisture. The composite conductive layer includes a binder phase formed by a polymer adhesive and conductive fillers fixed in the binder phase. At least some of the conductive fillers overlap each other, thereby forming a conductive path in the composite conductive layer.

[0023] In this process, the conductive filler is fixed within the binder phase, but it is not required that the conductive filler be completely embedded in the polymer binder. The conductive filler can be partially embedded in the binder phase, partially located on the surface of the binder phase, or in contact with or overlapping each other within the binder phase. The polymer binder is mainly used to maintain the spatial position of the conductive filler on the surface of the manufactured sand, while conductivity is primarily provided by the contact or overlap between the conductive fillers.

[0024] In this application, manufactured sand refers to sand particles or fine aggregates mainly containing silica or silicate components. It serves as the particle matrix of conductive manufactured sand, supporting the subsequently formed composite conductive layer. Manufactured sand can be artificial sand obtained from crushed, shaped, and screened rocks. The particle size of manufactured sand can be from 0.08 mm to 5 mm, and the silica content can be 50% to 75%. When the particle size is within this range, the manufactured sand can be used as fine aggregate in cement mortar or concrete, and also has sufficient outer surface for the conductive coating liquid to adhere. By selecting the above-mentioned type and particle size range of manufactured sand, the resulting conductive manufactured sand can be better adapted to the aggregate gradation of conventional cement-based materials, and the composite conductive layer can be distributed within the cement-based material along with the aggregate particles.

[0025] When performing the first microwave irradiation coupled with alkaline activation treatment on manufactured sand, the sand can be placed in a sodium hydroxide solution or potassium hydroxide solution and stirred and washed. The concentration of the sodium hydroxide solution or potassium hydroxide solution can be from 0.5 mol / L to 2 mol / L. The first microwave irradiation coupled with alkaline activation treatment includes placing the manufactured sand in an alkaline solution and activating it under microwave irradiation conditions for 1 to 10 minutes, making the surface of the manufactured sand more suitable for the subsequent spreading and adhesion of the conductive coating liquid. During the treatment, the alkaline solution is in full contact with the outer surface of the manufactured sand, and the gaps between the sand grains are constantly renewed by stirring, so that the surface of each sand grain can be affected by the alkaline solution. After this treatment, the wettability and surface activity of the manufactured sand surface are improved, and the subsequent conductive coating liquid is more easily covered on the surface of the manufactured sand. It can be understood that the alkaline activation treatment can provide a better surface foundation for the adhesion of the composite conductive layer and help improve the uniformity of the distribution of the conductive coating liquid on the sand grain surface. The purpose of microwave irradiation is to significantly shorten the alkaline activation time. If only the manufactured sand is activated with alkaline solution, the activation time needs to last for several hours. After microwave irradiation treatment, activated manufactured sand can be obtained by irradiation treatment for 1 to 10 minutes in the presence of alkaline solution. Specifically, the microwave irradiation power is 300 to 1000 W, and preferably, the irradiation treatment time can be further reduced to 2 to 8 minutes.

[0026] In the second microwave irradiation treatment, the power of the microwave irradiation treatment was 200~800W, and the irradiation time was 10~30s. After the second microwave irradiation treatment, the activated machine sand was dried.

[0027] Both microwave irradiation treatments can be performed using devices such as microwave reactors, microwave drying devices, or microwave ovens.

[0028] Alkali activation treatment can improve the wettability and surface activity of manufactured sand, making it easier for conductive coating liquid to spread and adhere to the surface of manufactured sand. It should be noted that the activation treatment does not require changes to the internal composition of the aggregate; it mainly acts on the outer surface of the manufactured sand.

[0029] After alkaline activation treatment, the manufactured sand can be washed with water until neutral and then dried to obtain activated manufactured sand. Washing until neutral means rinsing the alkaline-treated manufactured sand with water until the washing solution is nearly neutral, thereby removing residual free alkali from the sand particles. The water can be deionized water, tap water, or other cleaning water that does not introduce significant impurities; deionized water is preferred. Drying can be carried out in an oven or in a ventilated environment; oven drying is preferred to ensure consistent processing. Washing reduces the impact of residual alkali on the dispersion of the subsequent conductive coating solution, and drying removes free water from the sand particles' surface, giving the activated manufactured sand a more stable surface state during the coating stage. This step makes the contact between the conductive coating solution and the activated manufactured sand more stable, thus facilitating the formation of a more continuous composite conductive layer.

[0030] After obtaining activated manufactured sand, a polymer binder, conductive filler, dispersant, and water are mixed to obtain a conductive coating liquid. The conductive coating liquid is an aqueous mixture used to carry the conductive filler and adhere it to the aggregate surface. Water acts as a dispersion medium, allowing the polymer binder, conductive filler, and dispersant to mix within the same system. The polymer binder is a polymeric component that forms a binder phase after drying, used to retain the conductive filler on the aggregate surface. The conductive filler provides charge transport pathways, introducing conductivity onto the sand grain surface. The dispersant is an additive used to improve the dispersion of the conductive filler in the aqueous system, reducing agglomeration and allowing the conductive filler to enter the conductive coating liquid more uniformly. By mixing these components, a conductive coating liquid that possesses both coating capability and conductive components can be obtained, thus providing a material basis for the subsequent formation of a composite conductive layer.

[0031] The polymer binder can be one or more of polyvinylpyrrolidone (PVP), polyvinyl alcohol (PVA), or polyacrylic acid (PAA). PVP is a water-soluble polymer that forms a relatively uniform polymer phase in water and remains on the aggregate surface as a binder phase after drying. PVA molecules contain numerous hydroxyl groups and can also participate in the formation of an aqueous binder system. PAA molecules contain carboxyl groups and can be used as a binding or dispersing auxiliary component. The aforementioned polymer binder is distributed together with the conductive filler in the conductive coating liquid. After the conductive coating liquid adheres to the surface of the activated manufactured sand, the polymer binder forms a binder phase as water is removed. The binder phase refers to the continuous or semi-continuous polymer phase formed by the polymer binder on the aggregate surface, which can retain the conductive filler on the activated manufactured sand surface. Therefore, the polymer binder can reduce the migration of the conductive filler during coating, drying, and subsequent use, thereby improving the stability of the composite conductive layer.

[0032] When polyacrylic acid is used as a polymer adhesive, water-soluble polyacrylic acid or a partially neutralized polyacrylic acid system can be selected. In the conductive coating solution, it forms a polymeric binder phase and retains the conductive filler. The degree of ionization, molecular chain state, and film-forming properties of polyacrylic acid can differ from those of sodium acrylate substances. In this application, the polyacrylic acid is preferably used in a form that can form a continuous or semi-continuous binder phase after drying.

[0033] The conductive filler can be one or more of graphene (GNP), graphene oxide (GO), carbon nanotubes (CNTs), and carbon black. Graphene can be a sheet-like carbon material, graphene oxide can be a graphene-like sheet material containing oxygen-containing functional groups, carbon nanotubes can be tubular carbon materials, and carbon black can be granular carbon materials. Different conductive fillers have different morphologies, but all can participate in the construction of conductive pathways as functional components in the composite conductive layer. For graphene, the sheets can form overlapping paths through edge contact, surface contact, or local overlap. For carbon nanotubes, the tubular structures can form transport paths through intersection, contact, or entanglement. For carbon black, the particles can form transport paths through mutual contact. For graphene oxide, its sheet structure can be distributed on the aggregate surface with the conductive coating liquid and form a composite surface layer together with the polymer binder. By adding the above-mentioned conductive fillers to the conductive coating liquid, conductive functional components can be introduced into the surface of the manufactured sand, giving the conductive manufactured sand a basis for forming surface conductive pathways.

[0034] In this application, the term "conductive filler overlapping to form a conductive path" refers to the charge transport path formed by the conductive fillers through contact, overlap, entanglement, aggregation, or proximity. For graphene or graphene oxide, overlapping can manifest as edge contact, surface contact, or local overlap between sheets; for carbon nanotubes, overlapping can manifest as intersection, contact, or entanglement between tubular structures; and for carbon black, overlapping can manifest as contact or aggregation between particles.

[0035] When graphene is used as the conductive filler, the graphene sheet diameter can range from 5 micrometers to 15 micrometers, and the thickness can range from 5 nanometers to 10 nanometers. The sheet diameter refers to the lateral dimension of the graphene sheet, and the thickness refers to the vertical dimension. When the sheet diameter is in the range of 5 to 15 micrometers, the graphene sheet can cover a certain area on the sand grain surface and can overlap with adjacent graphene sheets. When the thickness is in the range of 5 to 10 nanometers, the graphene has a thinner sheet structure, which is easily spread onto the surface of activated manufactured sand with the conductive coating liquid. By using graphene within this morphology range, more sheet overlap points can be formed with a lower dosage, which is beneficial for forming continuous or semi-continuous conductive pathways in the composite conductive layer.

[0036] When the conductive filler includes graphene oxide, the graphene oxide can be used in combination with graphene, carbon nanotubes or carbon black to improve the dispersion and interfacial bonding of the conductive filler in the aqueous system, and the graphene, carbon nanotubes or carbon black therein can jointly form a conductive pathway; in other embodiments, the graphene oxide can also be reduced and then used as reduced graphene oxide to participate in the construction of the conductive pathway.

[0037] The dispersant can be one or more of melamine-based dispersants, sodium dodecylbenzene sulfonate, and polycarboxylate superplasticizers. Melamine-based dispersants are water-based additives that improve particle dispersion. Sodium dodecylbenzene sulfonate is a surfactant commonly used to disperse carbon-based materials. Polycarboxylate superplasticizers are commonly used admixtures with dispersing properties in cement-based materials. In the conductive coating liquid, the dispersant acts between the conductive filler and the aqueous medium, making the conductive filler easier to disperse in water and reducing large-scale agglomeration among the conductive fillers. By adding a dispersant, the uniformity of the conductive coating liquid can be improved, resulting in a more uniform spatial distribution of the conductive filler when subsequently coated onto the surface of activated manufactured sand. Therefore, the dispersant can improve the continuity of the conductive filler distribution in the composite conductive layer and facilitate the formation of conductive pathways.

[0038] After mixing polymer binders, conductive fillers, dispersants, and water, the mixture can be treated with mechanical stirring and ultrasonic dispersion, or only one of these treatments. Mechanical stirring refers to using a stirring paddle, magnetic stirrer, or other stirring mechanism to drive the flow of the liquid system, causing macroscopic mixing of the components. Ultrasonic dispersion refers to using the micro-disturbance and cavitation effects generated by ultrasound in the liquid to further disperse agglomerated conductive fillers. Mechanical stirring can initially mix water, dispersant, polymer binder, and conductive fillers, while ultrasonic dispersion can further break up conductive filler agglomerates, resulting in a more uniform distribution of the conductive filler in the coating solution. By combining mechanical stirring and ultrasonic dispersion, the conductive coating solution can achieve good fluidity and coating uniformity, thus facilitating the uniform adhesion of the conductive filler to the surface of the activated mechanical sand.

[0039] In one specific embodiment, based on 1000 parts of manufactured sand, the conductive filler can be 1 to 5 parts, the polymer binder can be 5 to 15 parts, the dispersant can be 0.5 to 2 parts, and the water can be 20 to 60 parts. In this formulation, the manufactured sand is the main component to be coated, the conductive filler is the functional component that provides conductive pathways, the polymer binder is the component that forms the binder phase, the dispersant is the auxiliary component that improves the dispersion state, and the water is the medium required for dispersion and coating. When the amount of conductive filler is between 1 and 5 parts, it can provide conductive components for the composite conductive layer, while avoiding excessive conductive filler that would cause the coating liquid to be too thick or difficult to disperse. When the amount of polymer binder is between 5 and 15 parts, it can provide sufficient binder phase to hold the conductive filler, while avoiding excessive binder phase that would block the contact between the conductive fillers. When the amount of water is between 20 and 60 parts, it can give the conductive coating liquid a flow state suitable for wetting and coating sand particles. Thus, this formulation range can take into account the overlap of conductive filler, the retention of binder phase, and the workability of coating.

[0040] It should be noted that the mass fraction is based on the mass of the manufactured sand in a dry state, and water is measured by mass; when water is measured by volume, it can be converted to mass according to the density of water at room temperature.

[0041] In a preferred embodiment, 50 parts of water, 1.25 parts of melamine-based dispersant, and stirring are added to a container and stirred until dissolved. Then, 2.5 parts of graphene and 10 parts of polyvinylpyrrolidone (PVP) are added. The graphene can be GNP with a sheet diameter of 5 to 15 micrometers and a thickness of 5 to 10 nanometers, and the PVP can be PVP K30. The above mixture is first magnetically stirred for 1 hour to initially mix the components, and then ultrasonically dispersed at 300 watts for 1 hour to further disperse the graphene sheets in the aqueous system, resulting in a conductive coating liquid. In this conductive coating liquid, graphene acts as a conductive filler distributed in the system formed by PVP and water. PVP not only helps maintain the distribution of graphene in the system but also forms a binder phase in the subsequent process. Thus, the obtained conductive coating liquid is suitable for forming a graphene-containing wet coating layer on the surface of activated manufactured sand.

[0042] Subsequently, activated manufactured sand is mixed with a conductive coating liquid, allowing the conductive coating liquid to adhere to the surface of the activated manufactured sand. The activated manufactured sand consists of multiple dispersed sand particles, while the conductive coating liquid is an aqueous system containing conductive fillers and polymer binders. After mixing, the conductive coating liquid forms a wet coating layer on the outer surface of the sand particles. This wet coating layer already contains conductive fillers, thus the conductive functional components have been introduced into the surface area of ​​the sand particles during the coating stage. During mixing, the activated manufactured sand can be poured into the conductive coating liquid, or the conductive coating liquid can be sprayed or added to the activated manufactured sand, followed by stirring, tumbling, kneading, or roller mixing to ensure the conductive coating liquid contacts and wets the surface of the sand particles. Through this step, the conductive fillers can be distributed on the surface of the activated manufactured sand along with the conductive coating liquid, providing a positional basis for the subsequent formation of a composite conductive layer.

[0043] In laboratory preparation, pretreated and dried manufactured sand can be poured into a conductive coating solution and thoroughly stirred with a glass rod or stirring paddle to ensure that the surface of each sand grain is wetted by the conductive coating solution. For batch preparation, a drum mixer, paddle mixer, or planetary mixer can be used. Regardless of the equipment used, its purpose is to ensure that the conductive coating solution adheres to the sand grain surface as uniformly as possible. The more uniform the adhesion of the conductive coating solution, the less likely large areas of uncovered areas will appear in the subsequently formed composite conductive layer. Thus, the coating step can improve the integrity of the conductive filler distribution on the sand grain surface and help the conductive manufactured sand obtain stable surface conductivity.

[0044] Subsequently, the activated manufactured sand coated with the conductive coating liquid undergoes a second microwave irradiation treatment. This fixes the conductive filler within the binder phase formed by the polymer adhesive, creating a composite conductive layer on the surface of the activated manufactured sand, resulting in conductive manufactured sand. It's important to note that the second microwave irradiation treatment does not induce conductivity in the conductive filler itself, but rather removes moisture from the conductive coating liquid, transforming it from a wet coating layer into a stable composite conductive layer adhered to the sand grain surface. During the second microwave irradiation process, moisture is gradually removed, the activated manufactured sand is dried, and the polymer adhesive remains on the surface of the activated manufactured sand, forming a binder phase. The conductive filler is retained within or on the surface of this binder phase. Thus, the conductive filler no longer exists merely as a suspension in the liquid but is stably maintained on the sand grain surface, thereby giving the conductive manufactured sand a retainable surface conductive structure.

[0045] During the second microwave irradiation treatment, the surface temperature of the activated manufactured sand is 60–100°C, and the time is 10–30 seconds. When the surface temperature of the activated manufactured sand is within this range, moisture in the conductive coating solution can be removed under relatively mild conditions, and the polymer binder can form a binding phase. When the time is within this range, the wet coating layer on the sand particle surface can be dried sufficiently, while avoiding excessive processing time that could affect production efficiency. By controlling the temperature and time, a composite conductive layer can be stably formed on the surface of the activated manufactured sand, thereby improving the surface layer stability of the conductive manufactured sand during subsequent transfer, mixing, and use.

[0046] In the composite conductive layer, at least some conductive fillers overlap to form conductive pathways. A conductive pathway refers to a charge transport path formed between conductive fillers through contact, overlap, interlocking, or proximity. For graphene, interlocking can manifest as edge contact, surface contact, or local overlap between sheets. For carbon nanotubes, interlocking can manifest as the crossing and entanglement between tubular structures. For carbon black, interlocking can manifest as contact between particles. Because at least some conductive fillers form the aforementioned conductive pathways in the composite conductive layer, individual conductive manufactured sand particles can acquire surface conductivity. When multiple conductive manufactured sand particles are distributed and close to each other in cement-based materials, the composite conductive layers on the surfaces of each particle can collectively participate in the construction of a macroscopic conductive network. Thus, the overlapping structure of the conductive fillers directly contributes to the conductivity of the conductive manufactured sand, while the binder phase formed by the polymer adhesive helps maintain the stable existence of this overlapping structure on the aggregate surface.

[0047] The conductive manufactured sand obtained by the above preparation method comprises manufactured sand and a composite conductive layer located on the surface of the manufactured sand. The composite conductive layer comprises a binder phase formed by a polymer binder and conductive fillers fixed in the binder phase. The conductivity of this conductive manufactured sand originates from the conductive fillers in the composite conductive layer, rather than from the manufactured sand itself. The polymer binder is used to hold the conductive fillers in place on the surface of the manufactured sand, the conductive fillers form conductive pathways by overlapping each other, and the activated manufactured sand provides a bearing surface. Together, these three components form a composite structure of aggregate matrix, binder phase, and conductive fillers from the inside out. Because the conductive fillers are fixed on the aggregate surface, the conductive manufactured sand can more stably retain its surface conductive structure when subsequently mixed with cement, water, and admixtures, thereby facilitating the construction of a stable conductive network in cement-based materials.

[0048] Understandably, the resulting conductive manufactured sand can be used as fine aggregate in mortar or concrete preparation. In use, the conductive manufactured sand can be mixed with cement and water, molded, and cured using conventional methods. The conductive manufactured sand is distributed within the cement-based material along with the fine aggregate, and its surface composite conductive layer can participate in the formation of a conductive network within the material. When the cement-based material is subjected to pressure, deformation, or damage, the contact state or transmission path of the conductive network changes, causing the material to exhibit a change in resistance. Since the conductive filler is mainly located on the aggregate surface, the conductive manufactured sand can utilize the spatial distribution of the aggregate itself within the cement-based material to participate in the construction of the conductive network. Therefore, conductive manufactured sand can be used to prepare conductive manufactured mortar, conductive concrete, or self-sensing cement-based materials, and can be used in scenarios such as structural health monitoring, road load sensing, or component damage early warning.

[0049] This application also provides a conductive manufactured sand, which is prepared by the aforementioned method.

[0050] In summary, compared with the prior art, this application has at least the following beneficial effects.

[0051] This application improves the stability of the conductive layer on the surface of conductive manufactured sand. First, the manufactured sand is activated with an alkaline solution to make its surface more suitable for wetting and adhesion of the conductive coating liquid. Then, the activated manufactured sand is coated with a conductive coating liquid containing a polymer binder and conductive filler. A second microwave irradiation treatment causes the polymer binder to form a bonding phase on the surface of the activated manufactured sand, and the conductive filler is fixed in this bonding phase. Thus, the conductive filler no longer relies solely on simple physical adsorption to remain on the aggregate surface, but is maintained on the manufactured sand surface by the bonding phase formed by the polymer binder. This improves the bonding stability between the composite conductive layer and the manufactured sand, reducing the possibility of the composite conductive layer detaching from the aggregate surface during subsequent mixing, transportation, or molding. Especially in embodiments where the polymer binder is polyvinylpyrrolidone (PVP) and the conductive filler is graphene, PPVP can interact with both the surface of the manufactured sand and the surface of the graphene, making the graphene more stably maintained on the aggregate surface. Ultrasonic vibration and water immersion tests show that the conductive layer on the surface of the conductive manufactured sand prepared in this way shows no significant peeling, and its stability is superior to the control sample without polymer binder or using other bonding systems.

[0052] This application improves the conductivity of conductive manufactured sand. The conductive filler is placed on the surface of activated manufactured sand, and a binder phase formed by a polymer adhesive holds the conductive filler within a composite conductive layer, allowing at least some of the conductive filler to overlap and form conductive pathways on the aggregate surface. When the conductive filler is graphene, the graphene sheets can form continuous or semi-continuous sheet-overlapping structures on the surface of the manufactured sand, thereby giving the originally high-resistivity manufactured sand surface conductivity. When mortar specimens are prepared using the conductive manufactured sand of this application, the composite conductive layer on the surface of the conductive manufactured sand can distribute along with the aggregate within the mortar and participate in the construction of a conductive network, significantly reducing the resistivity of the mortar specimen and demonstrating a resistance change response during stress. Under the test conditions of the examples, the resistivity of mortar specimens prepared using the conductive manufactured sand of this application is reduced by more than two orders of magnitude compared to ordinary mortar specimens, with a resistance change rate exceeding 43%.

[0053] The preparation process of this application is simple and cost-controllable. This application mainly includes steps such as alkaline activation treatment of manufactured sand, preparation of conductive coating solution, coating, and a second microwave irradiation treatment. The process flow is simple, and the required equipment can be conventional stirring equipment, ultrasonic dispersion equipment, and drying equipment, facilitating laboratory preparation and mass production. Furthermore, this application concentrates the conductive filler on the surface of the manufactured sand, rather than directly dispersing a large amount of conductive filler throughout the cement matrix, thus improving the utilization efficiency of the conductive filler. In some embodiments, the amount of conductive filler can be controlled to 0.1% to 0.5% of the mass of the manufactured sand, lower than the amount of conductive filler typically required in traditional direct blending methods, thereby helping to reduce material costs and minimize the adverse effects of high-volume conductive filler on the fluidity and mechanical properties of cement-based materials.

[0054] The conductive manufactured sand obtained in this application exhibits good compatibility with cement-based materials. Using manufactured sand as the matrix, the resulting conductive manufactured sand retains its granular fine aggregate morphology, enabling it to participate as fine aggregate in the preparation of cement mortar or concrete. The conductive filler is held on the aggregate surface by a binder phase formed by a polymer adhesive, eliminating the need for extensive free dispersion in the cement paste and thus reducing the agglomeration of the conductive filler in the cement matrix. Particularly in embodiments employing a composite conductive layer formed by polyvinylpyrrolidone and graphene, the polyvinylpyrrolidone / graphene composite layer on the surface of the conductive manufactured sand can stably cover the aggregate surface. This imparts conductivity to the conductive manufactured sand while maintaining its stability when used as fine aggregate in the preparation of cement-based materials, thereby contributing to the acquisition of self-sensing cement-based materials with stable electrical response.

[0055] Example 1 This embodiment provides a method for preparing conductive manufactured sand. The method involves selecting manufactured sand, improving its surface state through a first microwave irradiation coupled with an alkaline solution activation treatment, then coating the activated manufactured sand with a conductive coating solution containing graphene, polyvinylpyrrolidone, melamine-based dispersants, and water. Finally, a second microwave irradiation treatment is performed to form a composite conductive layer on the surface of the activated manufactured sand, thereby obtaining conductive manufactured sand.

[0056] Take 1350 grams of manufactured sand. Manufactured sand is artificial sand obtained by crushing, shaping and screening rocks. Its silica content is 50% to 75% and its particle size is 0.08 mm to 5 mm.

[0057] The manufactured sand was placed in a 1 mol / L sodium hydroxide solution to wet its surface, and then subjected to a first microwave irradiation coupled with alkaline activation treatment. Specifically, a microwave oven with adjustable power (600 watts) was used for the treatment, with an irradiation time of 5 minutes. After treatment, the manufactured sand was filtered out, rinsed with deionized water until the washing solution was neutral, and then dried for later use to obtain activated manufactured sand.

[0058] In a separate beaker, add 50 mL of deionized water, 1.25 g of melamine-based dispersant, and stir to dissolve. Then add 2.5 g of graphene and 10 g of polyvinylpyrrolidone (PVP). The graphene sheets have a diameter of 5 to 15 micrometers and a thickness of 5 to 10 nanometers. The PVP is PVP K30. Stir the mixture on a magnetic stirrer for 1 hour at 500 rpm, then transfer it to an ultrasonic disperser and ultrasonically disperse it at 300 watts for 1 hour to obtain the conductive coating solution.

[0059] The activated manufactured sand was poured into the conductive coating liquid and stirred thoroughly to wet and coat the surface of the sand. Then, the activated manufactured sand coated with the conductive coating liquid underwent a second microwave irradiation treatment at a power of 500 watts for 20 seconds. This caused polyvinylpyrrolidone to form a binder phase under microwave action, and graphene was fixed within the binder phase to form a composite conductive layer on the surface of the activated manufactured sand, resulting in conductive manufactured sand.

[0060] In this conductive manufactured sand, graphene is distributed and fixed in a binder phase formed by polyvinylpyrrolidone, and at least some of the graphene sheets overlap to form conductive pathways, thus giving the conductive manufactured sand surface conductivity. After a second microwave irradiation treatment, the conductive manufactured sand, denoted as GP, is obtained.

[0061] Example 2 This embodiment provides another method for preparing conductive manufactured sand. The preparation process of this embodiment is basically the same as that of Example 1, except that the polyvinylpyrrolidone in Example 1 is replaced with an equal mass of polyvinyl alcohol, while the other raw material types, raw material amounts, conditions for the first microwave irradiation coupled alkaline solution activation treatment, mechanical stirring conditions, ultrasonic dispersion conditions, and coating methods are the same as those in Example 1.

[0062] Specifically, in this embodiment, the conductive coating solution is formed by mixing deionized water, melamine-based dispersant, graphene, and polyvinyl alcohol, followed by mechanical stirring and ultrasonic dispersion. Polyvinyl alcohol, acting as a polymer binder, is distributed alongside graphene in the conductive coating solution and forms a binder phase on the surface of the manufactured sand after a second microwave irradiation treatment. Graphene, as a conductive filler, is retained within the binder phase formed by polyvinyl alcohol, with at least some graphene sheets overlapping to form conductive pathways. Thus, a composite conductive layer containing graphene and polyvinyl alcohol is formed on the surface of the manufactured sand, resulting in conductive manufactured sand, denoted as G-PVA.

[0063] This embodiment illustrates that, in addition to polyvinylpyrrolidone, polyvinyl alcohol can also be used as a polymer binder in the construction of conductive coating liquids and form a binder phase for retaining conductive fillers.

[0064] Comparative Example 1 This comparative example provides a method for preparing a control conductive machined sand. The preparation process of this comparative example is basically the same as that of Example 1, except that no polymer binder is added when preparing the conductive coating solution. Only deionized water, melamine dispersant and graphene are used to form a graphene-containing coating system. Other alkaline activation treatment conditions, mechanical stirring conditions, ultrasonic dispersion conditions and coating methods are the same as those in Example 1.

[0065] Specifically, after being activated with alkali, washed to neutral with water, and dried, the manufactured sand is mixed with a coating system containing graphene and melamine-based dispersants. Graphene can then adhere to the surface of the manufactured sand along with the liquid. After irradiation treatment and drying, a graphene-containing surface layer is formed on the sand grains. However, because this surface layer lacks a binder phase formed by a polymer adhesive, the graphene mainly adheres to the surface of the manufactured sand through its own adhesion to the sand grains, lacking a polymer binder phase to maintain the graphene's position. The resulting control conductive manufactured sand is designated G-NP.

[0066] This comparative example, compared with Example 1, illustrates the role of the polymer adhesive in maintaining the conductive filler and improving the stability of the composite conductive layer.

[0067] Comparative Example 2 This comparative example provides another method for preparing a control conductive mechanical sand. The preparation process of this comparative example is basically the same as that of Example 1, except that the polyvinylpyrrolidone in Example 1 is replaced with an equal mass of epoxy resin. Other raw material types, raw material amounts, alkaline activation treatment conditions, mechanical stirring conditions, ultrasonic dispersion conditions, and coating methods are the same as those in Example 1.

[0068] Specifically, in this comparative example, the conductive coating solution was formed by mixing and dispersing deionized water, melamine-based dispersants, graphene, and epoxy resin. After coating and a second microwave irradiation treatment, a surface layer containing graphene and epoxy resin was formed on the surface of the manufactured sand, resulting in the control conductive manufactured sand, denoted as GE. Epoxy resin can participate in the retention of graphene on the sand particle surface to a certain extent, but the resin phase it forms may affect the effective overlap between graphene sheets, making it difficult for graphene to fully form continuous conductive pathways. Therefore, this comparative example is used to compare with Example 1 to illustrate that not all resins or adhesive systems can simultaneously achieve both conductive filler retention and conductive pathway formation.

[0069] Comparative Example 3 This comparative example provides another method for preparing a control conductive machined sand. The preparation process of this comparative example is basically the same as that of Example 1, except that the polyvinylpyrrolidone in Example 1 is replaced with an equal mass of sodium acrylate. The other raw material types, raw material amounts, alkaline activation treatment conditions, mechanical stirring conditions, ultrasonic dispersion conditions, and coating methods are all the same as those in Example 1.

[0070] Specifically, in this comparative example, the conductive coating solution was formed by mixing and dispersing deionized water, melamine-based dispersants, graphene, and sodium acrylate. After coating and a second microwave irradiation treatment, a surface layer containing graphene and sodium acrylate was formed on the surface of the manufactured sand, resulting in the control conductive manufactured sand, denoted as GS. Sodium acrylate can participate in the adhesion of graphene to the surface of sand particles, but its film-forming state differs from that of polyvinylpyrrolidone, which may lead to uneven distribution or insufficient retention of graphene on the surface of sand particles. Therefore, this comparative example is used to compare with Example 1 to illustrate that the type of polymer binder affects the fixation state of the conductive filler on the surface of manufactured sand and the stability of the composite conductive layer.

[0071] The above Examples 1 and 2 are embodiments of this application, wherein Example 1 uses polyvinylpyrrolidone as a polymer binder, and Example 2 uses polyvinyl alcohol as a polymer binder. Comparative Example 1 did not add a polymer binder, Comparative Example 2 used epoxy resin instead of polyvinylpyrrolidone, and Comparative Example 3 used sodium acrylate instead of polyvinylpyrrolidone. Through the above examples and comparative examples, the effects of the presence or absence of polymer binders and different adhesive systems on the retention state of conductive fillers, the continuity of composite conductive layers, and the stability of conductive manufactured sand can be compared.

[0072] Test case To verify the surface coating state, conductivity, and stability of the composite conductive layer of the conductive manufactured sand of this application, performance tests were conducted on the conductive manufactured sand GP prepared in Example 1, the control conductive manufactured sand GE prepared in Comparative Example 2, and the control conductive manufactured sand GS prepared in Comparative Example 3. GP is a conductive manufactured sand prepared using polyvinylpyrrolidone as a polymer binder and graphene as a conductive filler; GE is a control conductive manufactured sand prepared using epoxy resin instead of polyvinylpyrrolidone; and GS is a control conductive manufactured sand prepared using sodium acrylate instead of polyvinylpyrrolidone.

[0073] First, the macroscopic morphology of the three types of samples was observed. For example... Figure 2 As shown in the figure, visual observation reveals that some yellow sand particles are still exposed on the surface of the GS sample, indicating that its surface coating is not completely intact; the surface of the GE sample is entirely black, indicating that graphene can adhere to the surface of the sand particles; the surface of the GP sample is highly uniformly black, and no obvious areas of exposed sand particles were observed. These results indicate that under the test conditions, the conductive coating solution formed using polyvinylpyrrolidone can enable graphene to cover the surface of the manufactured sand more uniformly, which is beneficial for forming a fully covered composite conductive layer.

[0074] The surface microstructure of the three samples was further observed using scanning electron microscopy. The observation results are as follows: Figure 3 As shown, the GS sample surface exhibits numerous exposed sand grain areas, with only sporadic distribution of sheet-like graphene on the sand grain surface, indicating poor continuity of the conductive filler's coverage on the aggregate surface. The GE sample surface is covered by a colloidal graphene / epoxy resin composite layer, but the graphene sheet morphology is not obvious, suggesting that the resin phase formed by the epoxy resin may affect the effective overlap between graphene sheets. The GP sample surface shows large overlapping graphene sheets with relatively complete coverage and clear sheet edges. These microstructures indicate that polyvinylpyrrolidone (PVP) facilitates the formation of continuous or semi-continuous overlapping structures of graphene sheets on the manufactured sand surface, thereby promoting the formation of conductive pathways in the composite conductive layer.

[0075] Conductivity tests were conducted on the three samples mentioned above. Specifically, the conductive layer material scraped from the surface of the GS, GE, and GP conductive mechanical sand was made into thin sheets measuring 10 mm × 10 mm × 1 mm. These sheets were then connected in series with a 3-volt DC power supply and a small light bulb. The illumination state of the light bulb was used as a direct indicator of the conductivity of the conductive layer. The test results are as follows: Figure 4As shown, the sheet corresponding to the GP sample can make the light bulb emit a strong light, the sheet corresponding to the GS sample can only make the light bulb emit a weak light, and the sheet corresponding to the GE sample cannot light the light bulb at all. The above results indicate that under the test conditions, the composite conductive layer on the surface of the GP sample has better conductivity, indicating that the binder phase formed by polyvinylpyrrolidone can maintain at least some of the graphene sheets in an effective overlapping state while retaining the graphene.

[0076] like Figure 5 As shown, stability tests were conducted on the three samples. Specifically, 10 grams of each of the GS, GE, and GP samples were placed in 50 ml of deionized water, shaken vigorously for 5 minutes, and then subjected to ultrasonic vibration treatment. The ultrasonic power was 100 watts, and the ultrasonic frequency was 40 kHz. The color of the supernatant was observed at 0, 10, and 30 minutes of ultrasonic vibration. At 0 minutes of ultrasonic vibration, the supernatant of all three samples was clear and transparent. At 10 minutes of ultrasonic vibration, the supernatant of the GS sample turned light gray, indicating that the graphene / sodium acrylate layer on its surface had begun to detach from the sand grains; the supernatants of the GE and GP samples remained clear. At 30 minutes of ultrasonic vibration, the supernatant of the GS sample turned dark gray, the supernatant of the GE sample turned slightly grayish, and the supernatant of the GP sample remained basically clear. The above results indicate that under the test conditions, the composite conductive layer on the surface of the GP conductive manufactured sand has better bonding stability with the manufactured sand, and its resistance to ultrasonic ablation is superior to that of the GS and GE samples.

[0077] To further confirm the coverage of the conductive filler on the GP sample surface, Raman spectroscopy was performed on the surface of the GP conductive manufactured sand prepared in Example 1. The test results are as follows: Figure 6 As shown, the surface of GP conductive machine sand is at approximately 1582 cm. -1 A distinct G-peak appears at approximately 2700 cm. -1 A weak G' peak appeared at the [location], and the aforementioned characteristic peaks correspond to those of graphene powder; meanwhile, no obvious characteristic peaks of manufactured sand were observed on the surface of the GP conductive manufactured sand. These results indicate that graphene has covered the surface of the GP conductive manufactured sand and exists as a conductive filler in the surface region of the manufactured sand within the composite conductive layer. Figure 6 The term "manufactured sand" refers to untreated conventional manufactured sand.

[0078] Application examples The conductive manufactured sand GP prepared in Example 1 was used to prepare mortar specimens. Specifically, 1400g of cement, 560g of water, and 2800g of conductive manufactured sand were mixed and stirred, then shaped and cured for 28 days using conventional curing methods to obtain mortar specimens containing conductive manufactured sand. As a control, ordinary sand was used instead of conductive manufactured sand, and ordinary mortar specimens were prepared under the same mix proportion and curing conditions.

[0079] The resistivity of mortar specimens was tested after 28 days of curing. The test results showed that the resistivity of the mortar specimens prepared using conductive mechanical sand GP from Example 1 was 8.6 × 10⁻⁶. 3 The resistivity of the ordinary sand control group mortar specimen was 2.7 × 10 Ω·cm. 5 Ω·cm. This shows that, under the same testing conditions, the resistivity of the mortar specimen prepared using the conductive manufactured sand of this application is significantly lower than that of the ordinary mortar specimen, indicating that the composite conductive layer on the surface of the conductive manufactured sand can be distributed within the mortar along with the aggregate and participate in the construction of the conductive network.

[0080] Further cyclic compression tests were conducted on mortar specimens prepared using the conductive manufactured sand GP from Example 1, and the resistance changes during loading were recorded. The resistance change rate FCR was calculated as FCR = ΔR / R0 × 100%, where R0 is the initial resistance of the mortar specimen before loading, and ΔR is the resistance change of the mortar specimen during loading. The test results showed that the resistance change rate of the mortar specimen prepared using the conductive manufactured sand GP from Example 1 under cyclic compression conditions reached 43.3%. This result indicates that the conductive manufactured sand of this application can induce a significant electrical response in the mortar specimen during stress, making it suitable for preparing cement-based materials with self-sensing functions.

[0081] The above are merely specific embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Those skilled in the art should understand that the present invention includes, but is not limited to, the contents described in the accompanying drawings and the specific embodiments above. Any modifications that do not depart from the functional and structural principles of the present invention will be included within the scope of the claims.

Claims

1. A method for preparing conductive manufactured sand, characterized in that, Includes the following steps: The manufactured sand was subjected to a first microwave irradiation coupled with alkaline solution activation treatment to obtain activated manufactured sand; The first microwave irradiation coupled alkaline solution activation treatment includes: placing the manufactured sand in an alkaline solution and performing activation treatment under microwave irradiation conditions for 1 to 10 minutes; A conductive coating liquid is obtained by mixing a polymer binder, a conductive filler, a dispersant and water, wherein the polymer binder is one or more of polyvinylpyrrolidone, polyvinyl alcohol or polyacrylic acid; The activated manufactured sand is mixed with the conductive coating liquid, so that the conductive coating liquid adheres to the surface of the activated manufactured sand; The activated mechanical sand with the conductive coating liquid attached is subjected to a second microwave irradiation treatment for 10-30 seconds. The conductive filler is fixed in the adhesive phase formed by the polymer adhesive after microwave irradiation and drying to form a composite conductive layer on the surface of the activated mechanical sand, thereby obtaining the conductive mechanical sand. In this embodiment, at least some of the conductive fillers overlap each other to form a conductive path.

2. The method for preparing conductive manufactured sand according to claim 1, characterized in that, The alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution, and the concentration of the sodium hydroxide solution or the potassium hydroxide solution is 0.5-2 mol / L; in the first microwave irradiation coupled alkaline solution activation treatment, the microwave irradiation power is 300-1000 W, and the irradiation treatment time is 2-8 min.

3. The method for preparing conductive manufactured sand according to claim 1, characterized in that, In the second microwave irradiation treatment, the power of the microwave irradiation treatment is 200~800W.

4. The method for preparing conductive manufactured sand according to claim 1, characterized in that, After the first microwave irradiation coupled alkaline solution activation treatment, the manufactured sand is washed with water until neutral and dried to obtain the activated manufactured sand; the manufactured sand is artificial sand obtained by crushing, shaping and screening rocks, with a silica content of 50% to 75% and a particle size of 0.08 to 5 mm.

5. The method for preparing conductive manufactured sand according to claim 1, characterized in that, The conductive filler is one or more of graphene, graphene oxide, carbon nanotubes, and carbon black.

6. The method for preparing conductive manufactured sand according to claim 5, characterized in that, When the conductive filler is graphene, the graphene sheet diameter is 5–15 μm and the thickness is 5–10 nm.

7. The method for preparing conductive manufactured sand according to claim 1, characterized in that, The dispersant is one or more of melamine dispersants, sodium dodecylbenzenesulfonate, or polycarboxylic acid water-reducing agents; the polymer binder, the conductive filler, the dispersant, and water are mixed and then subjected to mechanical stirring and / or ultrasonic dispersion treatment to obtain the conductive coating liquid.

8. The method for preparing conductive manufactured sand according to claim 1, characterized in that, By weight, the manufactured sand is 1000 parts, the conductive filler is 1-5 parts, the polymer binder is 5-15 parts, the dispersant is 0.5-2 parts, and the water is 20-60 parts.

9. The method for preparing conductive manufactured sand according to claim 1, characterized in that, During the second microwave irradiation treatment, the temperature of the activated mechanical sand surface is 60–100°C.

10. A conductive manufactured sand, characterized in that, The conductive manufactured sand is prepared by the method for preparing conductive manufactured sand according to any one of claims 1 to 9.